Android GIS-Based Information System Applying Dijkstra Algorithm For Finding The Nearest Tourist Spots in Sumenep District - Khairil Anam; Muhammad Yunus (IJCONSIST JOURNALS, 2019)
Abstract— Sumenep is listed in the eastern end of Madura Island. It takes more than four hours to reach Sumenep by bus or taxi from Surabaya. Sumenep has some interesting sites to visit. Besides historical sites like Kraton, Traditional Art and Cultural Attractions as Mask Dance and Bull Race, it also has beautiful beaches to see, such as; Lombang beach, Slopeng beach, Sembilan beach, Gili Labak and Gili Iyang which have the best oxygen levels in the world. However, mostly first visitors have a little bit difficulty to get information about it because the lack of detail information and schedule when the even held. In order to give brief information about it, researcher conduct the study which build an Android-based Geographic Information System using the Dijkstra Algorithm, which is expected to help them in displaying routes from one tourist spot to another. The Author applied the shortest route search algorithm, Dijkstra's algorithm, because this method can calculate the closest distance, both the distance between one tourist spot to another tourist spot, as well as the distance between the position of the user to the tourist place in the city of Sumenep.